2002
DOI: 10.1038/sj.bdj.4801448
|View full text |Cite
|
Sign up to set email alerts
|

The changing patterns of drinking, illicit drug use, stress, anxiety and depression in dental students in a UK dental school: a longitudinal study

Abstract: Objective To investigate alcohol and illicit drug use in a cohort of dental undergraduates through to VT year. Setting A UK dental school (with a medical school comparison group). Subjects and methods A cohort of dental students anonymously completed a lifestyle questionnaire about drinking and smoking, illicit drug use, stress, anxiety and depression in the spring of 1995 and 1998 as second and final year undergraduate students respectively, and in the summer of 1999 after one year working as qualified dentis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
104
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 12 publications
(1 reference statement)
12
104
2
3
Order By: Relevance
“…Lower prevalence of depression than reported in a longitudinal study by Newbury-Birch (13) on second- and fifth- year students was found in the present study. Like us, they found no differences between both years.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Lower prevalence of depression than reported in a longitudinal study by Newbury-Birch (13) on second- and fifth- year students was found in the present study. Like us, they found no differences between both years.…”
Section: Discussioncontrasting
confidence: 79%
“…Little attention has been paid to depression among dental students. The results of studies conducted on clinical years ranged between 2.8 and 15%, and between 7.4 and 14% on preclinical years (9,13,14), using different instruments and cutoff values to screen for depression. Considering gender, the abovementioned authors reported that more female than male dental students showed positive results for depression in clinical and preclinical years, except for Takayama (2), who found no gender differences among students in preclinical years.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,18,19 Previous studies have shown that dentistry can be a stressful occupation; 20,21 research on the sources of this stress may be able to assist early prevention and intervention initiatives. This study aimed to study sources of stress and strategies for managing stress among general dentists in Kerman.…”
Section: Discussionmentioning
confidence: 99%
“…This problem may be linked to the type of activities undertaken by medical students, associated with the level of academic pressure, workload, and burnout [1114]. Indeed, substance abuse, including over consumption of alcohol, is regarded a method of stress reduction among national and international medical students [15,16], and medical students have been reported to consume alcohol at levels exceeding the recommended guidelines [17,18]. …”
Section: Introductionmentioning
confidence: 99%